Police officers and post-traumatic stress disorder: Discussing the deficit in research, identification and prevention in England and Wales. (March 2019) - Foley, Jim; Massey, Kristina
This article will review available literature regarding post-traumatic stress disorder (PTSD) within policing in England and Wales, with a particular focus on its early identification and prevention. An overview of PTSD will be given as well as an exploration of why police officers are potentially more susceptible to this mental health condition compared to other members of society. Key factors in the early identification and prevention of PTSD will be outlined, with a focus on crisis intervention techniques which have been subject to considerable academic study. There is limited research available from England and Wales that looks specifically at PTSD in policing; this research deficit will be highlighted and key areas of research which need to be explored further will be given so that this problem can be both identified and prevented in officers.